Insights Into the Processing of Collocations During L2 English Reading: Evidence From Eye Movements - Li, Hui; Paterson, Kevin B.; Warrington, Kayleigh L.; Wang, Xiaolu (Frontiers in Psychology, 2022)
We report an eye movement experiment investigating effects of collocation strength and contextual predictability on the reading of collocative phrases by L2 English readers. Thirty-eight Chinese English as foreign language learners (EFL) read 40 sentences, each including a specific two-word phrase that was either a strong (e.g., black coffee) or weak (e.g., bitter coffee) adjective-noun collocation, and was either highly predictable or unpredictable from the previous sentence context. Eye movement measures showed that L2 reading times for the collocative phrases were sensitive to both collocation strength and contextual predictability. However, an interaction effect between these factors, which appeared relatively late in the eye movement record, additionally revealed that contextual predictability more strongly influenced time spent reading weak compared with strong collocations. This was most likely because the greater familiarity of strong collocations facilitated their integration, even in the absence of strong contextual constraint. We discuss the findings in terms of the value of collocations in second language learning.